Faktor-Faktor yang Mempengaruhi Mutu Pelayanan Rekam Medis di Rumah Sakit - Rindi Rendarti (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Background: Medical record units as part of supporting medical services in hospitals have an important role in improving the quality of services in hospitals. The indicator of service quality in hospital is measured by incomplete inpatient medical record files. Based on several studies in various hospitals, the complete of inpatient medical record files is around 70% - 80% from 100%. Based on the preliminary data in action research in PKU Muhammadiyah hospital, there were 60 % incomplete in filling the medical resume from 100% target. There are many things that occurred, one of them are about human resources that is affected by behavior, the implementation of operational standards in filling medical records, punish and reward files. Objective: To review the factors that affect the quality of service in medical record units related to improving the quality of hospital services.  Methods: the method of this study used relevant health databases including Scholars by using a combination of  terms: hospital service quality indicators, incompleteness in filling medical medical records, quality of medical record services. Results: The result of this study said that there were related between medical record services and quality of hospital services. The quality indicator in the medical record can be able to be measured was the number of incomplete filling in medical record files. Filling of incomplete medical record files has the potential to reduce the overall quality of hospital services Keywords: quality of medical record services, quality of hospital medical services, incomplete medical record filling